2022
DOI: 10.3390/e24050719
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Stochastic Differential Equation Approach for Spreading of Diseases

Abstract: The nonlinear fractional stochastic differential equation approach with Hurst parameter H within interval H∈(0,1) to study the time evolution of the number of those infected by the coronavirus in countries where the number of cases is large as Brazil is studied. The rises and falls of novel cases daily or the fluctuations in the official data are treated as a random term in the stochastic differential equation for the fractional Brownian motion. The projection of novel cases in the future is treated as quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The stochasticity impacts the outcomes of the model. Moreover, even a slight modification in the parameter value can result in chaotic dynamics, potentially leading to the occurrence of a disease outbreak [23].…”
Section: Introductionmentioning
confidence: 99%
“…The stochasticity impacts the outcomes of the model. Moreover, even a slight modification in the parameter value can result in chaotic dynamics, potentially leading to the occurrence of a disease outbreak [23].…”
Section: Introductionmentioning
confidence: 99%
“…[5]. The modeling based in the fractional stochastic differential equation has been used in [3,[6][7][8]. The stochastic dynamics smoking with non-Gaussian noise was studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional stochastic differential equations (FSDE) can be employed to model the spread of infectious diseases, including the COVID-19. These equations incorporate both fractional calculus and stochastic elements, allowing for the inclusion of long-range dependence and random fluctuations in the modeling process [1][2][3][4][5][6][7][8][9][10][11]. However, the use of fractional calculus in epidemiology is a relatively advanced and specialized approach.…”
Section: Introductionmentioning
confidence: 99%
“…An instance of this can be found in [21], where this approach is combined with linearization, resulting in a closed-form solution for stochastic differential equations (SDEs). The commonly employed Brownian motion process is typically stationary, although some authors have explored the utilization of fractional Brownian motion, as demonstrated in [17]. This concept is crucial in that it disrupts the typical independence of changes within a process and is particularly useful for cyclic growth patterns, notably in disease modeling.…”
Section: Introductionmentioning
confidence: 99%